THE MU’ALAMAH DROPSHIPPING SYSTEM: ISLAMIC ECONOMIC PERSPECTIVE - Hendri Hermawan Adinugraha; Mukhtarom Mukhtarom; Ali Muhtarom (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2021)
This research aims to explain the mu’alamah dropshipping system from an Islamic economic perspective. This study uses a literature or library research method which is sourced from authoritative data and sources, such as books and journals that are still relevant to the focus and discussion of this research. The results of the study concluded that allowing transactions that continue to develop in progress in the economy as long as they do not violate and do not contradict Islamic principles, dropshipping transactions which have now become a custom in society are allowed as long as the perpetrator understands the procedures for transactions, because the system is vulnerable and leads to the cancellation of a contract, namely selling goods that do not belong to him, and the development of technology greatly influenced the development of legal edicts that urged them to be issued. However, on many sides, with the legal norms that have been summarized by previous scholars by looking at the equality of legal ‘illat, it can be found that fast and precise legal answers can be found to determine the law in every legal event for which there is no clear legal provision in al- Qur'an and as-Sunnah.